Project Ada: Championing Women in Computer Science - Dal Pizzol, Natália; Musse, Soraia Raupp (Anais do Women in Information Technology (WIT), 2023)
Women have historically been underrepresented in STEM fields, including Computer Science. This article presents an overview of Project Ada, an initiative to empower women to pursue a career in Computer Science. The project, a partnership between a private university and a private sector company, funds scholarships to female students and provides support throughout their college careers. We hope this report will inspire more organizations and individuals to support similar initiatives and help bridge the gender gap in Computer Science and other STEM fields.